The vascular adventitia: An endogenous, omnipresent source of stem cells in the body - Woersdoerfer, Philipp; Mekala, Subba Rao; Bauer, Jochen; Edenhofer, Frank; Kuerten, Stefanie; Erguen, Sueleyman (Pharmacology & Therapeutics, 2017)
Until a decade ago it was believed that the wall of adult blood vessels exclusively contains terminally differentiated cell types. A paradigm shift was unavoidable since studies from different groups convincingly showed the presence of vascular wall-resident stem and progenitor cells (VW-SCs) which were identified to particularly reside in the sub-endothelial space and the so-called adventitial “vasculogenic zone”. Data published during the last decade uncloaked the fact that VW-SCs have the capacity to differentiate into both vascular and non-vascular cell types. Up to date, little is known about the full capacity of VW-SCs, the exact composition of their endogenous niche and the mechanisms that govern their self-renewal, activation and differentiation. The aim of this review is to provide an overview about the current knowledge on VW-SCs and to highlight the impact of this endogenous niche on health and disease. In addition, we will discuss strategies how these adult stem cells could be manipulated in order to activate and expand them, ideally within their niche at sites of tissue damage and subsequently differentiate them into a desired cell type, e.g. an endothelial cell, a macrophage or a muscle cell. This would pave the way towards new pharmacological strategies for endogenous tissue repair and regeneration.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Adventitia; Cardiomyocytes; Hematopoietic stem cells; Macrophages; Microglia; Vascular stem cells